REMEDIASI MISKONSEPSI MENGGUNAKAN MODEL PEMBELAJARAN LEVELS OF INQUIRY TENTANG TEKANAN SMP NEGERI 16 PONTIANAK - Iis Kholifah; Edy Tandililing; Syukran Mursyid (Universitas Tanjungpura, 2019)
Abstract The purpose of conducting this research is to know the effectiveness of the levels of inquiry learning model in remediating the misconception of students of Junior High School 16 in Pontianak about pressure material. The form of this research is one group pretest-posttest design. The sample of this research was VIII B. This class consisted of 30 students. The sample was designated by using purposive sampling technique. The data collection was diagnostic test through pre-test and post-test. The mean of percentage in the pre-test was 63.3% and the post-test was 22 %. The mean of student misconception decrease was 77%. Based on the DQM test, the effectiveness of remediation was 65% (Medium level). The result of the Mc Nemar test was obtained 31.25 of is higher than 3.84 of . There was a significant result after remedial misconceptions by using levels of inquiry learning model on the pressure material The teachers are expected to use this learning model levels of inwquiry as an alternative media to remediate student’s misconceptions on pressure material. Keywords: Learning Model, Levels of Inquiry, Misconception, Pressure, Remediation